Autopsy Findings- A Unique Case of Homicidal Strangulation - Saha , N (Journal of Indian Academy of Forensic Medicine, 2023)
To present and share, the classical autopsy findings of a unique case of homicidal strangulation. After meticulous scrutiny of relevant  documents, autopsy was carried out at Kolkata Police Morgue, using standard autopsy protocol and ancillary investigations. Still  photographs were taken observing standard protocol of Forensic Photography. A 62 year old man was found lying in a pool of blood, in  injured condition. A long cloth was found behind his neck, in untied condition, which gave an initial suspicion of a case of ligature  strangulation. Face, neck and fingernails, cyanosed. Blood on wearing apparel, noted. Hematoma over frontal region of scalp was present.  Both eyelids, both ears, nose and both lips, ware bruised. Nasal bones, fractured. Evidence of multiple nail scratch abrasions over anterior  aspect of the neck but no ligature mark could be found after careful examination. On dissection, strap muscles of neck, were bruised. On  opening the thorax, thyroid and cricoid cartilages, ware found bruised and left greater cornu of hyoid bone showing inward compression  fracture. Manual strangulation/throttling cases are not uncommon in a tertiary hospital morgue and usually a common method of  committing homicide. Meticulous autopsy examination can solve riddles that may lead to erroneous conclusions, as presented in this case.
Keywords: Ligature; Manual strangulation; Homicidal